The FCRL3 −169T>C polymorphism might be associated with some autoantibody presence in patients with SLE in a Polish population. Issue 2 (March 2014) - Piotrowski, Piotr; Lianeri, Margarita; Prokop, Edyta; Wudarski, Mariusz; Olesińska, Marzena; Jagodziński, Paweł P.
Abstract Objectives. The Fcrl3 −169T>C (rs7528684) polymorphism has been shown to be a risk factor of various autoimmune diseases, including systemic lupus erythematosus (SLE); however, these results are inconsistent between distinct ethnicities. Methods. Using PCR-RFLP we studied the distribution of the FCRL3 −169T>C polymorphism in SLE patients (n = 263) and controls (n = 528) in a sample from the Polish population. Results. We found no significant differences of FCRL3 −169T>C genotypes and alleles between patients with SLE and healthy individuals. However, in the dominant model we found a significant association between the FCRL3 −169T>C polymorphism and the presence of anti-Scl-70 antibody (Ab) [OR = 4.747 (95 % CI = 1.639–13.749), p = 0.0011, pcorr = 0.0198]. Moreover, in the dominant model we observed a significant contribution of FCRL3 −169T>C to the presence of either anti-La or anti-Scl-70 Abs [OR = 4.378 (95 % CI = 1.793–10.690, p = 0.0003, pcorr = 0.0054)]. Conclusions. Our study demonstrated that the FCRL3 −169T>C polymorphism is not a risk factor of SLE in the Polish population, but this polymorphism may contribute to autoantibody production in this disease.